Research progress of systematic nursing intervention on cancer-related fatigue (癌因性疲乏系统性护理干预研究进展) - DOU Yan (窦燕); ZHANG Xiaoning (张晓宁); CUI Yufeng (崔玉枫); ZHANG Liying (张丽莹); LIU Chunzi (刘春梓) (中西医结合护理)
Cancer-related fatigue is a severe form of fatigue among people with cancer, influencing the treatment outcome and quality of life of the patient. This paper reviewed the studies about cancer-related fatigue and related systematic nursing interventions, and provided evidence for establishment of systematic nursing model suited to national circumstances. (癌因性疲乏(CRF)在癌症患者中普遍存在, 严重影响患者治疗和生活质量。本研究综述CRF与系统护理干预的相关概念, 总结相关护理干预措施, 旨在为进一步探讨和建立适合我国国情的系统性护理干预模式提供参考。)